Effect of deformation and crystal size of mechanically alloyed and tempered composite tungsten powders with titanium additives on the sintering process - Jahangiri, H.; Ovecoglu, M.L. (Functional Materials, 2018)
The effect of the deformation and size of crystals of mechanically alloyed and tempered composite tungsten powders with titanium additives on the sintering process is studied. For the synthesis of composite powders W-xTi (x = 4.0 and 10.0 wt.%), The mechanical alloying process was carried out in a SpexTM Duo Mixer/Mill 8000D under an argon atmosphere for 20 h. The density and size of he crystallites/powders were measured before and after the quenching process. The measurements were carried out by a helical pycnometer and Lorentz methods in combination with XRD. Sintered bulk composites were characterized under the same conditions. Samples made by hardened powders did not fully cake. The relative density of sintered samples obtained from non-carbon powders was higher (97.19 %). In contrast, samples made from heat-treated powders had smaller crystallite sizes and lower densities (80.50 %). It is shown that the preheating of mechanically doped powders adversely affects the sintering of composite powders during the compaction process.